2021
DOI: 10.3389/fspor.2021.661167
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prioritizing Lead or Boulder Climbing Among Intermediate Climbers

Abstract: This study compared the effects of prioritizing lead climbing or boulder climbing on climbing-specific strength and endurance, as well as climbing performance. Fourteen active climbers were randomized to a boulder climbing training group (BCT: age = 27.2 ± 4.4 years, body mass = 65.8 ± 5.5 kg, height = 173.3 ± 3.8 cm) or a lead-climbing training group (LCT: age = 27.7 ± 6.1 years, body mass = 70.2 ± 4.4 kg, height = 177.7 ± 4.4 cm). The groups participated in a 5-week training period consisting of 15 sessions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 28 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…The fingers are typically positioned in a half-crimp grip on a climbing hold, likely providing a more sport-specific condition compared to handheld dynamometers (Ozimek et al, 2016;Marcolin et al, 2020). This and similar set-ups have displayed (1) ability to discriminate between performance levels (Grant et al, 1996;MacLeod et al, 2007), and (2) changes in finger strength following a training period (Stien et al, 2021a). Researchers have suggested that climbing-specific maximal strength and RFD tests performed standing on the ground with fixed elbows produced more reliable results (ICC = 0.94) compared to performing the tests with fully extended elbows (ICC = 0.88) (Michailov et al, 2018).…”
Section: Isolated Forearm Testsmentioning
confidence: 89%
See 3 more Smart Citations
“…The fingers are typically positioned in a half-crimp grip on a climbing hold, likely providing a more sport-specific condition compared to handheld dynamometers (Ozimek et al, 2016;Marcolin et al, 2020). This and similar set-ups have displayed (1) ability to discriminate between performance levels (Grant et al, 1996;MacLeod et al, 2007), and (2) changes in finger strength following a training period (Stien et al, 2021a). Researchers have suggested that climbing-specific maximal strength and RFD tests performed standing on the ground with fixed elbows produced more reliable results (ICC = 0.94) compared to performing the tests with fully extended elbows (ICC = 0.88) (Michailov et al, 2018).…”
Section: Isolated Forearm Testsmentioning
confidence: 89%
“…Still, handheld dynamometers have been reliable (Baláš et al, 2012;Medernach et al, 2015a), and able to discriminate between climbers and non-climbers (Quaine et al, 2003;Macdonald and Callender, 2011;Limonta et al, 2015;Assmann et al, 2020). Recently, tests that closely mimic the hold types and arm positions in climbing have been implemented (Levernier and Laffaye, 2019;Baláš et al, 2021;Rokowski et al, 2021;Stien et al, 2021a). Using climbingspecific test set-ups rather than handheld dynamometers could be especially important when assessing training effects and comparing different performance levels.…”
Section: Dynamometer Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cord had to be completely taut before the test began and no kipping with the legs or creating a countermovement were allowed. The force-time curves criteria have been described previously (Stien et al, 2021a ). The participants had to hang still on the rung (no more than ±5 N fluctuation in force for 1,000 ms) before exerting maximal force (Stien et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%